Oral health in postmenopausal and premenopausal women after myocardial infarction in Poland: a preliminary study - Górski, Bartłomiej; Ganowicz, Ewa; Górska, Renata (Menopause Review/Przegląd Menopauzalny, 2015)
Introduction: Age and hormonal disorders are recognized factors impacting the periodontium and the prevalence of cardiovascular diseases, but as yet the relationship between these two conditions in postmenopausal (post-M) and premenopausal (pre-M) women in Poland has not been assessed. The aim of this study was to compare the periodontal status in women after myocardial infarction (MI) with women without MI history and to determine risk factors for periodontitis. Material and methods : The study included 35 women hospitalized due to MI, average age 54.7 ± 9.4 years, and 96 women randomly drawn from the general population, average age 56.1 ± 10.0 years. All women were checked for periodontitis risk factors (education, socioeconomic status, tobacco smoking, stress), and underwent dental examination. Results: The lowest number of teeth was found in post-M women after MI (median = 8), whereas pre-M women without MI history had 25 teeth. Edentulousness occurred more frequently in post-M women compared with pre-M women (12.2% vs. 0%), the same was observed for advanced periodontitis (28.4% vs. 21.1%). The severity of periodontitis was highest in the post-M subgroup (more than half demonstrated advanced periodontitis or edentulousness). The most important risk factor for periodontitis, regardless of age, was the level of education. In post-M women the second risk factor was smoking, while in pre-M women negative stress. Conclusions : The status of oral health in post-M women is unsatisfactory, particularly in those affected by cardiovascular diseases. It is necessary to take preventive and educational measures targeted at these women.